2014
DOI: 10.1186/2008-2231-22-26
|View full text |Cite
|
Sign up to set email alerts
|

The effect of adipose derived stromal cells on oxidative stress level, lung emphysema and white blood cells of guinea pigs model of chronic obstructive pulmonary disease

Abstract: BackgroundChronic obstructive pulmonary disease (COPD) is a worldwide epidemic disease and a major cause of death and disability. The present study aimed to elucidate pharmacological effects of adipose derived stromal cells (ASCs) on pathological and biochemical factors in a guinea pig model of COPD. Guinea pigs were randomized into 5 groups including: Control, COPD, COPD + intratracheal delivery of PBS as a vehicle (COPD-PBS), COPD + intratracheal delivery of ASCs (COPD-ITASC) and COPD + intravenous injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 32 publications
2
17
1
Order By: Relevance
“…Increased interalveolar septum, presence of lymphatic tissue in the lung parenchyma, destruction of alveolar wall, and existence of emphysema in the lung and intra-alveolar bleeding of lungs were also observed in guinea pig models of COPD following exposure to CS [50, 51, 5457]. In another study, airway and parenchymal neutrophilia, increased goblet cell numbers, lung hydroxyproline content, airway wall collagen and airspace size, were reported [69].…”
Section: Measured Parametersmentioning
confidence: 97%
See 2 more Smart Citations
“…Increased interalveolar septum, presence of lymphatic tissue in the lung parenchyma, destruction of alveolar wall, and existence of emphysema in the lung and intra-alveolar bleeding of lungs were also observed in guinea pig models of COPD following exposure to CS [50, 51, 5457]. In another study, airway and parenchymal neutrophilia, increased goblet cell numbers, lung hydroxyproline content, airway wall collagen and airspace size, were reported [69].…”
Section: Measured Parametersmentioning
confidence: 97%
“…Total WBC [51] and eosinophil counts in blood were increased in guinea pig models of CS-induced COPD [50, 53]. Total WBC, eosinophils and neutrophils in lung lavage of COPD guinea pigs were also increased [52].…”
Section: Inflammatory Cells and Mediatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we used cigarette smoke exposure to induce of animal model of COPD. Several previous studies have shown that consecutive cigarette smoke exposure can successfully induce the COPD in rats [7][8][9] . This study clearly demonstrated that consecutive induction of cigarette smoke can lead to the significantly distinctive change of COPD and lung inflammatory in rats.…”
Section: Table2 the Results Of Total Wbc Numbers And The Percentage mentioning
confidence: 99%
“…The tissue was minced into small pieces and incubated for 40 min in PBS containing 2 mg/ml collagenase at 37°C with mild agitation [21,22]. After centrifuging, the floated adipocytes were discarded and the stromal cells were suspended in DMEM medium supplemented with 10% fetal bovine serum, 100 U/ml penicillin and 100 μg/ml streptomycin and cultured in flask.…”
Section: Methodsmentioning
confidence: 99%